2001
DOI: 10.1113/jphysiol.2001.012917
|View full text |Cite
|
Sign up to set email alerts
|

Function and expression of the epithelial Ca2+ channel family: comparison of mammalian ECaC1 and 2

Abstract: 1. The epithelial Ca(2+) channel (ECaC) family represents a unique group of Ca(2+)-selective channels that share limited homology to the ligand-gated capsaicin receptors, the osmolarity-sensitive channel OTRPC4, as well as the transient receptor potential family. Southern blot analysis demonstrated that this family is restricted to two members, ECaC1 and ECaC2 (also named CaT1). 2. RT-PCR analysis demonstrated that the two channels are co-expressed in calbindin-D-containing epithelia, including small intestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
215
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(225 citation statements)
references
References 0 publications
8
215
2
Order By: Relevance
“…The inactivation of TRPV6 is characterized by a slow decline after an initial fast inactivation phase, whereas TRPV5 only shows the slow inactivation phase (Nilius et al 2001a. In line with a Ca 2+ -dependent regulation is the observation that chelation of intracellular Ca 2+ with ethylene glycol-bis(b-aminoethyl ether)-N,N,N′,N′-tetra acetic acid (EGTA) or 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid acethoxymethylester (BAPTA) resulted in increased channel activity (Bodding and Flockerzi 2004;Hoenderop et al 2001b;Peng et al 1999). Together, these data indicate that intracellular Ca 2+ exerts a negative feedback mechanism on TRPV5 and TRPV6 activity.…”
Section: Ca 2+ -Dependent Inactivationmentioning
confidence: 87%
See 1 more Smart Citation
“…The inactivation of TRPV6 is characterized by a slow decline after an initial fast inactivation phase, whereas TRPV5 only shows the slow inactivation phase (Nilius et al 2001a. In line with a Ca 2+ -dependent regulation is the observation that chelation of intracellular Ca 2+ with ethylene glycol-bis(b-aminoethyl ether)-N,N,N′,N′-tetra acetic acid (EGTA) or 1,2-bis(2-aminophenoxy)ethane-N,N,N′,N′-tetraacetic acid acethoxymethylester (BAPTA) resulted in increased channel activity (Bodding and Flockerzi 2004;Hoenderop et al 2001b;Peng et al 1999). Together, these data indicate that intracellular Ca 2+ exerts a negative feedback mechanism on TRPV5 and TRPV6 activity.…”
Section: Ca 2+ -Dependent Inactivationmentioning
confidence: 87%
“…Electrophysiological studies using human embryonic kidney cells (HEK293), heterologously expressing TRPV5 or TRPV6, show that both channels are permeable for monovalent and divalent cations with a high selectivity for Ca 2+ (Gunthorpe et al 2002;Hoenderop et al 2001b;Vennekens et al 2002). The characteristic pore region of TRPV5 and TRPV6 is unique for its high Ca 2+ selectivity, in which a single aspartic residue at position number 542 (D542) is crucial for Ca 2+ permeation Vennekens et al 2001).…”
Section: Molecular Features Of Trpv5 and Trpv6mentioning
confidence: 99%
“…The identity of the apical calcium channel in distal tubule remains somewhat controversial; Hoenderop et al (119) did not detect CaT1 RNA in human kidney RNA using RT-PCR but did find abundant ECaC RNA, while Peng et al (120,121) found evidence of CaT1 RNA in human kidney RNA as well as ECaC, localized to distal nephron. Abundance studies using real-time PCR suggest that CaT1 RNA is more abundant than ECaC RNA in kidney (122).…”
Section: Dent Disease (X-linked Recessive Nephrolithiasis) Dent and mentioning
confidence: 99%
“…Application of 600 M 2-APB resulted in Ca 2ϩ oscillations in olfactory bulb astrocytes, suggesting activation of TRP channels. Addition of 10 M ruthenium red, which also acts as a TRPV inhibitor (30), suppressed the generation of Ca 2ϩ oscillations, although an initial Ca 2ϩ transient was elicited frequently upon incubation with 2-APB/ruthenium red (Fig. 4C).…”
Section: Gabaa Receptors Mediate Ca 2؉ Signaling In Neurons But Not Inmentioning
confidence: 99%